Challenges and Concerns for Toilets Access among Adolescent Girls in an Urban Slum -A Viewpoint - Abhiruchi Galhotra; Utsav Raj (Medsci Publications, 2019)
Indian cities are experiencing rapid population growth and expansion of urban poor. Many of these people live in informal settlements which are areas of high density, poor quality housing-the 'poverty pockets' with inadequate provision of basic water and sanitation services. Sanitation in slums poses the dual risk of increased disease incidence, on one hand, and it raises the issue of personal safety, security, and dignity of women and girls on the other hand. A community toilets (CT) facility is a shared facility provided for a defined group of residents or an entire settlement/community. Women, despite having a high demand for safe toilet facilities, continue to practice unsafe sanitation. In response to the shame and fear associated with open defecations, women restrict their mobility. To ensure safe, accessible and long-term usability of community toilets, it is critical to select the most appropriate location and community toilet design.